PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN FINANCIAL RATIO TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2020-2024) - Mukhamad Ramadhan Aryo Handoko; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2026)
This study aims to examine and analyze the effect of Corporate social responsibility (CSR) and financial ratios, which consist of profitability and leverage, on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. CSR and financial ratios, including profitability and leverage, are important factors that can influence tax policy and the long-term sustainability of companies.The research method used is quantitative with purposive sampling technique. Data were obtained from the companies' annual reports and sustainability reports, with independent variables including CSR, financial ratios consisting of profitability and leverage, each proxied by Return on Assets (ROA) and Debt to Asset Ratio (DAR), and the dependent variable, tax avoidance, measured by Effective Tax Rate (ETR). The data were analyzed using multiple linear regression.The results indicate that CSR has a significant positive effect on tax avoidance, showing that companies with strong commitments to social responsibility are more likely to engage in aggressive tax avoidance practices, thus hypothesis 1 is rejected. Additionally, profitability, measured by ROA, also has a positive effect on tax avoidance, indicating that companies with higher profit levels tend to be make tax avoidance, thus hypothesis 2 is rejected. In contrast, leverage, measured by Debt to Asset Ratio (DAR), does not have a significant effect on tax avoidance, indicating that a company's debt structure does not influence its tendency to engage in tax avoidance practices, thus hypothesis 3 is rejected.